PENGARUH KESEHATAN KERJA DAN KESELAMATAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. PLN (Persero) UP3 BENGKULU - Syaputra, Hatifa; Bahrun, Khairul (Yayasan Insani Mandiri Santani, 2020)
The purposes of this study were to determine the effect of occupational healthand work safety toward employees’ performance at PT. (Persero) UP3 Bengkulu. This research was conducted from January 20 to February 32020 at PT. PLN (Persero) UP3 Bengkulu. The population of this study were employees at PT. PLN (Persero) UP3 Bengkulu, amounting to 63 people by using quantitative methods.This research used several data analysis techniques such as instrument testing, classic assumption tests, respondent response analysis, multiple linear regression analysis, determinant coefficients, and hypothesis testing. The results of the research indicate that the Occupational Health (X1) and Work Safety (X2) variables, partially or simultaneously affect the employees’performance (Y) at PT. PLN (Persero) UP3 Bengkulu. It was proved by the results of multiple linear regression obtained a regression equation Y = 4.260 + 0.300 (X_1) + .368 (X2) and the hypothesis showed that Occupational Health (sig α = 0.000 <0.050), Occupational Safety (sig α = 0.000 <0.050) in other words simultaneously had a significant effect towardemployees’performance. Regarding the two variables occupational health and safety at the performance of employees at PT PLN (Persero) UP3 Bengkulu. Keywords: Occupational Health, Safety, Employees’ Performance